2000
DOI: 10.1016/s0550-3213(99)00659-8
|View full text |Cite
|
Sign up to set email alerts
|

Ricci-flat branes

Abstract: Up to overall harmonic factors, the D8-brane solution of the massive type IIA supergravity theory is the product of nine-dimensional Minkowski space (the worldvolume) with the real line (the transverse space). We show that the equations of motion allow for the worldvolume metric to be generalised to an arbitrary Ricci-flat one. If this nine-dimensional Ricci-flat manifold admits Killing spinors, then the resulting solutions are supersymmetric and satisfy the usual Bogomol'nyi bound, although they preserve fewe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
141
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(144 citation statements)
references
References 44 publications
1
141
0
2
Order By: Relevance
“…Since self-duality of the spin connection in seven dimensions implies that the 3-form defined in (26) is closed and co-closed and, therefore, G 2 holonomy (noted in [54,55], proved explicitly in [25] and used to rederive the metric of [49] in [56]) we have shown that our equations (30) (or equivalently (17), (18) and (21)) indeed describe a manifold of G 2 holonomy.…”
mentioning
confidence: 63%
“…Since self-duality of the spin connection in seven dimensions implies that the 3-form defined in (26) is closed and co-closed and, therefore, G 2 holonomy (noted in [54,55], proved explicitly in [25] and used to rederive the metric of [49] in [56]) we have shown that our equations (30) (or equivalently (17), (18) and (21)) indeed describe a manifold of G 2 holonomy.…”
mentioning
confidence: 63%
“…We use an iterative convergence scheme to relax the bulk equations (15). The finite differencing, boundary conditions and scheme details are stated in appendix 8.3.…”
Section: Numerical Schemementioning
confidence: 99%
“…These are the Ricci-flatness conditions given in [3,4,6]. Also the supersymmetry variations factorize in a part proportional to the projection operator of the p-brane and the following conditions on ǫ coming from the internal and external metrics:∇…”
Section: Ricci-flat Branes and Intersectionsmentioning
confidence: 99%